How are the phenologies of ripening and seed release affected by species' ecology and evolution?. Issue 5 (6th October 2016) - Heydel, Felix; Tackenberg, Oliver
Abstract : The phenology of seed ripening and release are important for dispersal, reproductive success and survival of plants. Most phenological studies, however, consider early phenological phases. Here, we examined the ecological and evolutionary basis of ripening and seed release phenology. We monitored single flower phenology for 104 plant species from 30 families and three life forms from central Europe. Further, we undertook an associate monitoring study along an elevational gradient over two years. We calculated temperature demands (as growing degree days) for ripening and seed release and examined them with respect to the species' seed mass, life form, dispersal mode and phylogeny. We found a strong correlation between species' seed mass and temperature demands for ripening. For both variables seed mass and temperature demands for seed ripening, we found a strong effect of the species phylogeny. These phylogenetic signals indicate that the evolutionary history of the species' lineage affects its seed mass and the temperature demands for seed ripening. Among the studied life forms, shrub species showed the most efficient ripening process. Anemochorous species showed lower relative humidity during seed release than epizoochorous species. For anemochorous species, the synchronisation of release timing with periods that show favourable environmental conditions for wind dispersal could be interpreted as a phenological adaptation to increase dispersal distances. According to the monitoring along the elevational gradient, individuals from higher altitudes showed lower temperature demands for ripening than individuals from lower altitudes. This might tentatively indicate physiological adaptations to lower temperature demands for locations with a shorter growing season. Our study provides basic insights into the ecological, environmental and evolutionary constraints that shape the ripening and seed release phenology of plants. We introduce data that can be used to advance existing models of ripening phenology, seed release and plant spread.